STANDAR OPERASIONAL PROSEDUR BIDANG â€œK3â€ PADA UNIT SARANA PT. KERETA API INDONESIA (PERSERO) DAERAH OPERASI 6 YOGYAKARTA - Widodo Hariyono (Teknoin, 2016)
One of the important programs of PT Kereta Api (Persero) in creating a quality product, both locomotives and railway carriages was to realize standard working system. Facility unit of Regional Operations (Daop) 6 Yogyakarta, had a very important role in determining the feasibility and readiness of locomotives and carriages before leaving, which indirectly determined the safety and comfort of passengers. Care of locomotives and carriages on a regular basis to maintain locomotives and carriages were always in optimal condition. Each worker of Unit Facility should understand and implement the SOP OHS that had been determined. SOP OHS could provide information to workers in order to carry out their duties and responsibilities with the safe and sound, so accidents and occupational diseases could be avoided, as well as to achieve the goals set by PT Kereta Api (Persero). Objective : This study aimed to determine the application of SOP OHS in Facility Unit of PT Kereta Api Indonesia (Persero) Daop 6 Yogyakarta. Methods : The method used in this study was descriptive qualitative. The subjects of this study included junior managers, supervisors, and workers carriage depot Yogyakarta, junior managers, supervisors, and workers locomotive depot Yogyakarta. Data were collected through interviews and direct observation. The data were analyzed descriptively by using triangulation of sources and methods. Results : The results showed that the policy of SOP OHS in the facility Unit of PT Kereta Api Indonesia (Persero) was created by team of Safety, Health, and Environment (SHE) which has been reviewed and adjusted to Occupational Health and Safety Management System and ISO 9001: 2008. The SOP OHS Policy in the Facility Unit included (1) Personal Protective Equipment (PPE), (2) the reporting and investigation of incidents, accidents and occupational diseases, (3) inspection of work, (4) signs of K3, (5) maintenance (6) emergencies. Worker’s understanding on the facility unit in the SOP OHS was good, but the worker’s adherence to SOP OHS should be improved. Conclusions: Application of SOP OHS in the facility unit of PT Kereta Api Indonesia (Persero) Daop 6 Yogyakarta has met the requirements, but there were some things that must be addressed and completed.